Mobility Justice for Persons With Disability: Body–Environment Interactions and Velomobility - Glen Norcliffe; John Radford (International Journal of Disability and Social Justice)
This article addresses a major source of inequality and exclusion in contemporary transport, namely the mobility injustices faced by persons with diverse forms of disability. Our focus is on one aspect, the potential for velomobility – using a range of adaptive cycles – to increase mobility and, therefore, access to education, work, recreation, social encounters, and to enjoy freedom. We pursue this topic by, first, advancing the notion of epistemic justice as the form of justice most appropriate for addressing this issue. Second, we outline some recent technical developments of adaptive cycles, suggesting that considerable progress has been made in managing a range of impairments such that technical blockages do not currently appear to be the main obstacles to the wider adoption of velomobility. We then examine socio-economic, political, environmental, and cultural constraints, suggesting these socially constructed blockages present the biggest obstacles to advancing velomobility for persons with disability who might otherwise gain the diverse therapeutic benefits.